Autophagy Plays an Important Role in Anti-inflammatory Mechanisms Stimulated by Alpha7 Nicotinic Acetylcholine Receptor - Shao, Bo-Zong; Ke, Ping; Xu, Zhe-Qi; Wei, Wei; Cheng, Ming-He; Han, Bin-Ze; Chen, Xiong-Wen; Su, Ding-Feng; Liu, Chong (Frontiers in Immunology, 2017)
Alpha7 nicotinic acetylcholine receptor (α7nAChR) has been reported to alleviate neuroinflammation. Here we aimed to determine the role of autophagy in α7nAChR-mediated inhibition of neuroinflammation and its underlying mechanism. Experimental autoimmune encephalomyelitis (EAE) mice and lipopolysaccharide (LPS)-stimulated BV2 microglia were used as in vivo and in vitro models of neuroinflammation, respectively. The severity of EAE was evaluated with neurological scoring. Autophagy-related proteins (Beclin 1, LC3-II/I, p62/SQSTM1) were detected by immunoblot. Autophagosomes were observed using transmission electron microscopy and tandem ﬂuorescent mRFP-GFP-LC3 plasmid was applied to test autophagy flux. The mRNA levels of interleukin-6 (IL-6), IL-1β, IL-18 and tumor necrosis factor-α (TNF-α) were detected by real-time PCR. We used 3-methyladenine (3-MA) and autophagy-related gene 5 small interfering RNA (Atg5 siRNA) to block autophagy in vivo and in vitro, respectively. Activating α7nAChR with PNU282987 ameliorates EAE severity and spinal inflammatory infiltration in EAE mice. PNU282987 treatment also enhanced monocyte/microglia autophagy (Beclin 1, LC3-II/I ratio, p62/SQSTM1, colocalization of CD45 or CD68 positive cells with LC3) both in spinal cord and spleen from EAE mice. The beneficial effects of PNU282987 on EAE mice were partly abolished by 3-MA, an autophagy inhibitor. In vitro, PNU282987 treatment increased autophagy and promoted autophagy flux. Blockade of autophagy by Atg5 siRNA or bafilomycin A1 attenuated the inhibitory effect of PNU282987 on IL-6, IL-1β, IL-18 and TNF-α mRNA. Our results demonstrate for the first time that activating α7nAChR enhances monocyte/microglia autophagy, which suppresses neuroinflammation and thus plays an alleviative role in EAE.